SOCIO-ECONOMIC AND PSYCHOLOGICAL CORRELATES OF FASHION CONSCIOUSNESS OF CONSUMERS - Syeda Azra Batool; Batool, Syeda Shahida; Atif Khan Jadoon (Journal of Arts & Social Sciences, 2021)
Fashion conscious people allocate a large part of their budget on a latest fashion. The present study assessed the socio-economic and psychological factors that play significant role in fashion consciousness. A convenient sample of 200 individuals (men=100 and women=100) of age between 22 and 44 years from Multan, Pakistan was taken to study the correlates of fashion consciousness. The estimates of ordinary least square showed that education, monthly income, materialism, and media exposure had significant positive impact, and price consciousness had significant negative impact on fashion consciousness of the sample, which partially support consumption theories (e.g., Absolute Income Hypothesis’ and ‘Relative Income Hypothesis). The study has implications for both consumers and producers.Key Words:  Fashion consciousness, materialism, price consciousness, absolute income hypothesis, relative income hypothesis